Effect of Lower Extremity Range of Motion (ROM) Exercise on Improving Blood Circulation - Basri, Basri; Arlis, Arlis; Yongki, Phan (Jurnal Keperawatan Priority, 2024)
Range of Motion Exercise (ROM) are used to increase peripheral perfusion with the aim of facilitating adequate oxygen diffusion and adequate supply of nutrients to the wound area and for the process of repairing wound tissue in the legs of diabetes mellitus patients. The aims to determine the effect of lower extremity range of motion (ROM) training on improving blood circulation in the legs of patients with type 2 diabetes mellitus at Aceh Singkil District Hospital. This Study design uses quasi experimental using a one group pre-test post-test design approach. The Study sample was 35 respondents. Data were analyzed using the Wilcoxon sign rank test. The results of the study showed that there was a significant effect on the blood circulation in the legs of type 2 diabetes mellitus patients before and after being given lower extremity Range of Motion (ROM) training with a value of p = 0.000, the average value before lower extremity ROM training was 1.28 with a minimum value of 1.00 and maximum 2.00. and after being given lower extremity ROM exercises the average value was 1.94 with a minimum value of 1.00 and a maximum value of 2.00. From the results of this Study, it is hoped that nurses at Aceh Singkil District Hospital can apply lower extremity exercises to reduce the risk of complications from peripheral vascular disease, especially in diabetes mellitus sufferers.